2002
DOI: 10.1139/p01-139
|View full text |Cite
|
Sign up to set email alerts
|

QED effective action revisited

Abstract: The derivation of a convergent series representation for the quantum electrodynamic effective action obtained by two of us (S.R.V. and D.R.L.) in [Can. J. Phys. 71, 389 (1993)] is reexamined. We present more details of our original derivation. Moreover, we discuss the relation of the electric-magnetic duality to the integral representation for the effective action, and we consider the application of nonlinear convergence acceleration techniques which permit the efficient and reliable numerical evaluation of th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
34
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(34 citation statements)
references
References 57 publications
(121 reference statements)
0
34
0
Order By: Relevance
“…This is a classic signal of instability, and corresponds precisely to the vacuum instability of vacuum pair production first noted by Heisenberg and Euler. This imaginary part can also be seen to arise from the poles on the real s axis encountered in the integral representation (1.23), which shows that this integral representation must be defined more carefully, with an approriate iǫ prescription [3,12]. From this integral representation, or from a Borel dispersion relation, it is straightforward to derive the full nonperturbative imaginary part of the Heisenberg-Euler effective Lagrangian to be:…”
Section: Spinor Qed Casementioning
confidence: 99%
See 1 more Smart Citation
“…This is a classic signal of instability, and corresponds precisely to the vacuum instability of vacuum pair production first noted by Heisenberg and Euler. This imaginary part can also be seen to arise from the poles on the real s axis encountered in the integral representation (1.23), which shows that this integral representation must be defined more carefully, with an approriate iǫ prescription [3,12]. From this integral representation, or from a Borel dispersion relation, it is straightforward to derive the full nonperturbative imaginary part of the Heisenberg-Euler effective Lagrangian to be:…”
Section: Spinor Qed Casementioning
confidence: 99%
“…and a and b are related to the Lorentz invariants a characterizing the background electromagnetic field strength [1]: If G = 0, it is possible to transform to a Lorentz frame in which the electric and magnetic fields are parallel or antiparallel, depending on the sign a There has been a notational reversal [3,8,62] of a ↔ b since the original Heisenberg-Euler paper [1]. I stick here with Heisenberg's original notation since in a frame in which B and E are parallel, we associate b ↔ B and a ↔ E, which seems more natural.…”
mentioning
confidence: 99%
“…The n th term in the sum directly relates to the probability for the coherent production of n pairs by the field [17,25]. Usually one derives the formula (1) by a proper treatment of the poles appearing in the standard integral representation of the one-loop Euler-Heisenberg lagrangian (see, e.g., [26,27]). Affleck et al showed in [24] that the same formula can be obtained in the spirit of instanton physics by a stationary phase appromixation of the corresponding worldline path integral.…”
Section: Introductionmentioning
confidence: 99%
“…Let us also recall that due to an electric-magnetic duality, the Heisenberg-Euler effective Lagrangian and the photon polarization tensor in a purely magnetic and a purely electric field are related and can be translated into each other [26,27]: the magnetic field result is converted into the corresponding electric field result by means of the transformations B ↔ −iE and ↔⊥. Hence, our result (4.20) for Π µν 2-loop (k|B) 1PR can be straightforwardly adapted to a purely electric field, yielding the exact expression for Π µν 2-loop (k|E) 1PR .…”
Section: -Loop Hementioning
confidence: 99%